Proposta de Roteirização para o Transporte Público Escolar de Araguaína - Tocantins - Mendonça, Alex Silva (Universidade Federal do Tocantins, 2024)
Public transport makes it possible to serve populations regarding their locomotion, providing a connection between different regions of a city, allowing the movement of people or goods. In the municipality of Araguaína, Tocantins, one of the main problems in public transport is the issue of delays and congestion on the main roads of the city. The purpose of this article is to implement a mathematical model to optimize a route for public school transport, based on the 17 public high schools in the city. In this modeling, the chosen approach was the Traveling Salesman Problem (TSP), which consists of tracing a shortest route, starting from a point, visiting all the others only once and returning to the point of origin. With the optimized route, it would be possible to travel the entire 30.8 km journey in approximately one hour, plus boarding and disembarking times. With proposals like this one, it would be possible to serve a large number of passengers and still generate savings in time and fuel, in addition to providing satisfaction to users, who could reach their desired destination more quickly.